2017
DOI: 10.1097/dss.0000000000001048
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Laser Therapy for the Treatment of Nonmelanoma Skin Cancer

Abstract: BACKGROUND Skin cancer remains the most prevalent type of cancer in the United States, and its burden on the health care system remains substantial. Standard treatments such as cryosurgery, electrodessication and curettage, topical and photodynamic therapies, and surgical excision including Mohs micrographic surgery are not without inherent morbidity, including risk of bleeding, infection, and scar. OBJECTIVE Lasers may be an alternative for treatment of nonmelanoma skin cancer, and this paper reviews this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 47 publications
0
39
0
2
Order By: Relevance
“…Upon light absorption, the PPIX then undergoes excitation, resulting in production of oxygen free radicals, ultimately leading to cancer cell death. [ 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 ]. PDT has shown to be effective in treating superficial BCC, SCCis, and actinic keratosis (AK) with excellent cosmesis, though, it is currently not recommended for invasive SCC and aggressive BCC subtypes such as basosquamous or morphoeic infiltrating types [ 110 , 111 ].…”
Section: Treatment Of Nmsc: Overview Of Surgical and Non-surgical mentioning
confidence: 99%
See 2 more Smart Citations
“…Upon light absorption, the PPIX then undergoes excitation, resulting in production of oxygen free radicals, ultimately leading to cancer cell death. [ 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 ]. PDT has shown to be effective in treating superficial BCC, SCCis, and actinic keratosis (AK) with excellent cosmesis, though, it is currently not recommended for invasive SCC and aggressive BCC subtypes such as basosquamous or morphoeic infiltrating types [ 110 , 111 ].…”
Section: Treatment Of Nmsc: Overview Of Surgical and Non-surgical mentioning
confidence: 99%
“…There are four major laser types used in the treatment of skin cancers: solid-state, diode, dye, and gas lasers [ 157 ]. A recent review article by Soleymani et al discusses the different types of laser treatments in detail [ 158 ]. This study demonstrated that vascular targeting pulse dye lasers (PDL) have shown promising results in different studies with a complete clinical response in up to 95% of patients; nevertheless, poor results were also seen.…”
Section: Treatment Of Nmsc: Overview Of Surgical and Non-surgical mentioning
confidence: 99%
See 1 more Smart Citation
“…An unusual case with rapid growth was recently reported by Corni et al, [8] but they did not observe recurrence or complications at a 6 months followup. Furthermore, though 15% of recurrence rate was noted in recent literature; [8,28] all of these cases had a benign natural history.…”
Section: Introductionmentioning
confidence: 90%
“…A legújabb adatok szerint alacsony kockázatú basaliomák esetén jól kiválogatott esetekben lehet terápiás alternatíva a széndioxid lézer egyéb kezeléssel (pl. fotodinámiás terápia) kombinálva (17)(18)(19).…”
Section: Táblázat Magyarországon Forgalomba Nem Lévő Aktinikus Keratunclassified